anonymous
  • anonymous
Given the sequence –3, 0, 3, which of the following is equivalent to:
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
\[\sum_{n=5}^{8}A -subscript- N\]
anonymous
  • anonymous
54 102 144 162
anonymous
  • anonymous
@primeralph @terenzreignz

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
@Zarkon
anonymous
  • anonymous
First term is -3, common difference is 0-(-3) = 3 So, the sequence is \[a_n = -3+3(n-1)\]
anonymous
  • anonymous
so, we can do that plugging n-2, n-3 etc. into the next equations?
anonymous
  • anonymous
[-3+3(n-1)]+[-3+3(n-2)] etc.?
anonymous
  • anonymous
You need to find sum from the fifth term to the eighth term, so, find a5, a6, a7, a8 and add them together.
anonymous
  • anonymous
n is the number of term
anonymous
  • anonymous
that's right we start on 5 right? so like this?
anonymous
  • anonymous
e.g. \[a_5 = -3+3(5-1)=...\]
anonymous
  • anonymous
Start from 5, yes.
anonymous
  • anonymous
[-3+3(n-5)]+[-3+3(n-6)]+[-3+3(n-7)]+[-3+3(n-8)]?
anonymous
  • anonymous
(-3+3n-15)+(-3+3n-18)+ (-3+3n-21)+ (-3+3n-24)?
anonymous
  • anonymous
am I doing this right?
anonymous
  • anonymous
(3n-18)+(3n-21)+(3n-24)+(3n-x)+(3n-27)
anonymous
  • anonymous
i'm not sure what to do from there
anonymous
  • anonymous
No
anonymous
  • anonymous
\[a_5 = -3+3(5-1)\]\[a_6 = -3+3(6-1)\]\[a_7 = -3+3(7-1)\]... Then, find \(a_5+a_6+a_7+a_8\)
anonymous
  • anonymous
=−3+3(5−1) =−3+3(6−1) =−3+3(7−1) =-3+3(8-1)
anonymous
  • anonymous
=-6+15 =-6+18 =-6+21 =-6+24 =9 =12 =15 =18 9+12+15+18
anonymous
  • anonymous
54
anonymous
  • anonymous
thank you so much guys

Looking for something else?

Not the answer you are looking for? Search for more explanations.